Static recovery process modelling of engineering metallic alloys - Ramasamy, Devarajan; Muhamad, Mat Noor; Azlyna, Senawi; Ahmad Syahrizan, Sulaiman (2008)
Static recovery annealing of cold worked metallic alloys will change mechanical properties without major changes in the elongated grains structure. A series of experiments have been carried out to investigate the effect of pre-strain, annealing time and annealing temperature on static recovery kinetics of aluminium-based alloys and copper-based alloys. The static recovery kinetics is then modelled using an empirical static recovery kinetic model. Analysis of activation energies of the above mentioned metallic alloys also suggests that static recovery process could be model using isochronal experimental data.